$${calculate}\:\:\int\:\:\:\:\:\:\frac{{dx}}{\left({x}^{\mathrm{2}} −\mathrm{1}\right)\sqrt{{x}^{\mathrm{2}} +\mathrm{2}}} \\$$
$${let}\:{I}\:=\int\:\frac{{dx}}{\left({x}^{\mathrm{2}} −\mathrm{1}\right)\sqrt{{x}^{\mathrm{2}} +\mathrm{2}}}\:\:{changement} \\$$$${x}=\sqrt{\mathrm{2}}{sh}\left({t}\right)\:{give}\:{I}\:=\int\:\:\:\frac{\sqrt{\mathrm{2}}{ch}\left({t}\right)}{\left(\mathrm{2}{sh}^{\mathrm{2}} {t}−\mathrm{1}\right)\sqrt{\mathrm{2}}{ch}\left({t}\right)}{dt} \\$$$$=\int\:\:\:\:\frac{{dt}}{\mathrm{2}\:\frac{{ch}\left(\mathrm{2}{t}\right)−\mathrm{1}}{\mathrm{2}}−\mathrm{1}}\:=\int\:\:\:\frac{{dt}}{{ch}\left(\mathrm{2}{t}\right)−\mathrm{2}} \\$$$$=\int\:\:\:\:\frac{{dt}}{\frac{{e}^{\mathrm{2}{t}} \:+{e}^{−\mathrm{2}{t}} }{\mathrm{2}}−\mathrm{2}}\:=\int\:\:\:\:\frac{\mathrm{2}{dt}}{{e}^{\mathrm{2}{t}} \:+{e}^{−\mathrm{2}{t}} −\mathrm{4}} \\$$$$=_{{e}^{\mathrm{2}{t}} ={u}} \:\:\:\:\int\:\:\:\:\frac{\mathrm{2}}{{u}+{u}^{−\mathrm{1}} −\mathrm{4}}\:\frac{{du}}{\mathrm{2}{u}}\:=\int\:\:\frac{{du}}{{u}^{\mathrm{2}} \:+\mathrm{1}−\mathrm{4}{u}} \\$$$$=\int\:\:\:\frac{{du}}{{u}^{\mathrm{2}} −\mathrm{4}{u}\:+\mathrm{1}} \\$$$${u}^{\mathrm{2}} −\mathrm{4}{u}\:+\mathrm{1}=\mathrm{0}\rightarrow\Delta^{'} =\mathrm{4}−\mathrm{1}=\mathrm{3}\:\Rightarrow{u}_{\mathrm{1}} =\mathrm{2}+\sqrt{\mathrm{3}} \\$$$${u}_{\mathrm{2}} =\mathrm{2}−\sqrt{\mathrm{3}}\:\Rightarrow{I}\:=\frac{\mathrm{1}}{\mathrm{2}\sqrt{\mathrm{3}}}\int\:\:\:\left(\frac{\mathrm{1}}{{u}−{u}_{\mathrm{1}} }−\frac{\mathrm{1}}{{u}−{u}_{\mathrm{2}} }\right){du} \\$$$$=\frac{\mathrm{1}}{\mathrm{2}\sqrt{\mathrm{3}}}{ln}\mid\frac{{u}−{u}_{\mathrm{1}} }{{u}−{u}_{\mathrm{2}} }\mid\:+{c}=\frac{\mathrm{1}}{\mathrm{2}\sqrt{\mathrm{3}}}{ln}\mid\frac{{u}−\mathrm{2}−\sqrt{\mathrm{3}}}{{u}−\mathrm{2}+\sqrt{\mathrm{3}}}\mid\:+{c} \\$$$$\frac{\mathrm{1}}{\mathrm{2}\sqrt{\mathrm{3}}}{ln}\mid\frac{{e}^{\mathrm{2}{t}} −\mathrm{2}−\sqrt{\mathrm{3}}}{{e}^{\mathrm{2}{t}} −\mathrm{2}+\sqrt{\mathrm{3}}}\mid\:+{c}\:\:{but}\:{we}\:{have} \\$$$${t}={argsh}\left(\frac{{x}}{\:\sqrt{\mathrm{2}}}\right)\:={ln}\left(\frac{{x}}{\:\sqrt{\mathrm{2}}}+\sqrt{\mathrm{1}+\frac{{x}^{\mathrm{2}} }{\mathrm{2}}}\right)\:\Rightarrow \\$$$${e}^{\mathrm{2}{t}} \:=\left(\frac{{x}}{\:\sqrt{\mathrm{2}}}+\sqrt{\mathrm{1}+\frac{{x}^{\mathrm{2}} }{\mathrm{2}}}\right)^{\mathrm{2}} \:\Rightarrow \\$$$${I}\:=\frac{\mathrm{1}}{\mathrm{2}\sqrt{\mathrm{3}}}{ln}\mid\frac{\frac{{x}+\sqrt{{x}^{\mathrm{2}} +\mathrm{2}}}{\:\sqrt{\mathrm{2}}}−\mathrm{2}−\sqrt{\mathrm{3}}}{\frac{{x}+\sqrt{{x}^{\mathrm{2}} +\mathrm{2}}}{\:\sqrt{\mathrm{2}}}−\mathrm{2}+\sqrt{\mathrm{3}}}\mid\:+{c} \\$$$$\\$$$$\\$$$$\\$$
$${I}\:=\frac{\mathrm{1}}{\mathrm{2}\sqrt{\mathrm{3}}}{ln}\mid\frac{\left(\frac{{x}+\sqrt{{x}^{\mathrm{2}} \:+\mathrm{2}}}{\:\sqrt{\mathrm{2}}}\right)^{\mathrm{2}} −\mathrm{2}−\sqrt{\mathrm{3}}}{\left(\frac{{x}+\sqrt{{x}^{\mathrm{2}} \:+\mathrm{2}}}{\:\sqrt{\mathrm{2}}}\right)^{\mathrm{2}} −\mathrm{2}+\sqrt{\mathrm{3}}}\mid\:+{c} \\$$